The Semiotics of Wealth and Status: A Peircean Triadic Reading of Indexical and Symbolic Signs in Jane Austen’s Pride and Prejudice - Ahmad Rizal Abdullah (Perkumpulan Dosen Muslim Indonesia, 2026)
This study investigates the structural mechanisms of socioeconomic dominance and gender dynamics in Jane Austen’s Pride and Prejudice. While previous research focuses heavily on macro-thematic or general feminist readings, there is a lack of systematic inquiry into how microtextual elements actively build and subvert these power structures. To fill this research gap, this study applies Charles Sanders Peirce’s triadic semiotic theory by analyzing the relationships between representamen, object, and interpretant across icons, indices, and symbols to decode physical assets, nominal values, and social behaviors within the text. Using a qualitative design based on document analysis and close reading, twenty key extracts were examined following the qualitative interactive framework of Miles, Huberman, and Saldaña. The findings reveal that quantifiable assets and elite landscapes, such as annual incomes and the Pemberley estate, operate as potent indexical signs that establish and legitimize class stratification. Concurrently, Regency social conventions and patriarchal inheritance laws function as rigid symbolic signs designed to enforce female submission. However, the semiotic interplay ultimately uncovers a powerful counter-narrative of resistance, where the heroine, Elizabeth Bennet, actively subverts these codes. By demanding to be treated as a rational creature, she activates the female gaze as a counter-power that validates female autonomy and dismantles patriarchal hegemony. This study concludes that operationalizing formal triadic semiotics can reveal deep, hidden ideological meanings about gender, wealth, and systemic control within classic realist literature.